2018
DOI: 10.1007/s42114-018-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

A review on thermally conductive polymeric composites: classification, measurement, model and equations, mechanism and fabrication methods

Abstract: With the fast-developing miniaturization and integration of microelectronics packaging materials, ultrahigh-voltage electrical devices, light-emitting diodes (LEDs), and in areas which require good heat dissipation and low thermal expansion, the investigations on the polymeric composites with highly thermal conductivities and excellent thermal stabilities are urgently required, which would be beneficial to transferring the heat to the outside of the products, finally to effectively avoid substantial overheatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
124
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 294 publications
(137 citation statements)
references
References 165 publications
(121 reference statements)
2
124
0
1
Order By: Relevance
“…[50][51][52][53][54][55][56][57] Researchers have shown that functionalized h-BN has high thermal conductivity, excellent thermal properties, and that it can be incorporated as a conductive ller in polymeric matrices. [58][59][60][61][62][63][64] Gu et al used NH 2 -POSS functionalized nBN llers to improve the thermal conductivities for PPS dielectric nanocomposites. 58 However, research on improving both the thermal conductivity and toughness of epoxy matrix is scarce and not widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52][53][54][55][56][57] Researchers have shown that functionalized h-BN has high thermal conductivity, excellent thermal properties, and that it can be incorporated as a conductive ller in polymeric matrices. [58][59][60][61][62][63][64] Gu et al used NH 2 -POSS functionalized nBN llers to improve the thermal conductivities for PPS dielectric nanocomposites. 58 However, research on improving both the thermal conductivity and toughness of epoxy matrix is scarce and not widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have found that thermal conductivity of nanofluids is determined by many factors. For example, the properties (size, shape, concentration, dispersibility, and surface charge) of nanoparticle, base fluids, temperature, and so on . The effects of base fluids refer to the property of base fluids and viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…The rapid development of electronic technology and the emergence of emerging industries have put higher requirement on the thermal performance of the traditional packaging materials [1][2][3][4]. Most polymers have the advantages of good processability, low cost and excellent insulation, etc, but the lower thermal conductivity of polymers (around 0.1-0.3 W m −1 K −1 ) limits the application in the field of thermally conductive packaging [5][6][7]. In order to ensure the great stability and lifetime in practical application of materials, thermally conductive fillers are widely used to improve the thermal conductivity of the composites [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%